Protecting child health and nutrition status with ready-to-use food in addition to food assistance in urban Chad: a cost-effectiveness analysis - Puett, Chloe (BioMed Central, 2013)
BACKGROUND: Despite growing interest in use of lipid nutrient supplements for preventing child malnutrition and morbidity, there is inconclusive evidence on the effectiveness, and no evidence on the cost-effectiveness of this strategy. METHODS: A cost effectiveness analysis was conducted comparing costs and outcomes of two arms of a cluster randomized controlled trial implemented in eastern Chad during the 2010 hunger gap by Action contre la Faim France and Ghent University. This trial assessed the effect on child malnutrition and morbidity of a 5-month general distribution of staple rations, or staple rations plus a ready-to-use supplementary food (RUSF). RUSF was distributed to households with a child aged 6–36 months who was not acutely malnourished (weight-for-height > = 80% of the NCHS reference median, and absence of bilateral pitting edema), to prevent acute malnutrition in these children. While the addition of RUSF to a staple ration did not result in significant reduction in wasting rates, cost-effectiveness was assessed using successful secondary outcomes of cases of diarrhea and anemia (hemoglobin <110 g/L) averted among children receiving RUSF. Total costs of the program and incremental costs of RUSF and related management and logistics were estimated using accounting records and key informant interviews, and include costs to institutions and communities. An activity-based costing methodology was applied and incremental costs were calculated per episode of diarrhea and case of anemia averted. RESULTS: Adding RUSF to a general food distribution increased total costs by 23%, resulting in an additional cost per child of 374 EUR, and an incremental cost per episode of diarrhea averted of 1,083 EUR and per case of anemia averted of 3,627 EUR. CONCLUSIONS: Adding RUSF to a staple ration was less cost-effective than other standard intervention options for averting diarrhea and anemia. This strategy holds potential to address a broad array of health and nutrition outcomes in emergency settings where infrastructure is weak and other intervention options are infeasible in the short-term. However, further research is needed to establish the contexts in which RUSF is most effective and cost-effective in preventing acute malnutrition and morbidity among vulnerable children, compared to other options.